Studi Tentang Sumber Kebisingan Dan Getaran Pada Kapal Kargo Serta Dampaknya Terhadap Kesehatan Awak Kapal - Agung Aulia, Dimas (PT Yupin Felicitas Utama, 2025)
Noise and vibration caused by ship engines and propulsion systems can cause various health problems for crew members, such as hearing loss, muscle pain, fatigue, and stress. This study uses a quantitative method with a case study approach on cargo ships operating in international waters. Noise measurements were carried out using a sound level meter, while vibration measurements used a vibration meter at three main points, namely the engine room, ship deck, and control room. In addition, questionnaires were given to 50 crew members to identify their health complaints. The results showed that the noise level in the engine room reached 85-100 dB, while the vibration level in the engine room was 1.2-1.8 m/s², which exceeded the safe limit recommended by WHO. The most common health impacts experienced by crew members were hearing loss (42%), muscle and joint pain (38%), and fatigue and insomnia (35%). This study recommends that shipping companies pay attention to the health aspects of crew members by introducing noise and vibration reduction policies, and providing adequate protection facilities. In addition, it is important to increase crew awareness of the health risks due to exposure to noise and vibration in the ship's work environment.